Assessing the Effects of Banana Pingers as a Bycatch Mitigation Device for Harbour Porpoises (Phocoena phocoena) - Omeyer, Lucy C. M.; Doherty, Philip D.; Dolman, Sarah; Enever, Robert; Reese, Allan; Tregenza, Nicholas; Williams, Ruth; Godley, Brendan J. (Frontiers in Marine Science, 2020)
Bycatch is a significant cause of population declines of marine megafauna globally. While numerous bycatch mitigation strategies exist, acoustic alarms, or pingers, are the most widely adopted strategy for small cetaceans. Although pingers have been shown to be an effective measure for numerous species, there are some concerns about their long-term use. Bycatch is recognised as a persistent problem in waters around Cornwall, United Kingdom, where several cetacean species are resident, with harbour porpoises (Phocoena phocoena) being the most-commonly sighted. In this study, we assessed the effects of a Banana Pinger (Fishtek Marine Limited) on harbour porpoises in Cornwall between August 2012 and March 2013. Two passive acoustic loggers (C-PODs; Chelonia Limited) were deployed 100m apart to record cetacean activity during cycles of active and inactive pinger periods. Harbour porpoises were 37% less likely to be detected at the C-POD near the pinger when the pinger was active, while they were only 9% less likely to be detected 100m further away. The effect of the pinger was constant over the study period at both C-PODs despite the temporal variation in harbour porpoise detections. In addition, we found no evidence of reduced pinger effect with changing environmental conditions. Furthermore, harbour porpoise detections at the C-POD near the pinger did not depend on the time elapsed since the pinger turned off, with harbour porpoises returning to the ensonified area with no delay. Together these results suggest that (1) harbour porpoises did not habituate to the pinger over an eight-month period, (2) the pinger effect is very localised, and (3) pinger use did not lead to harbour porpoise displacement over the study period, suggesting an absence of long-term behavioural effects. We suggest that the deployment of pingers on fishing nets would likely reduce net-porpoise interactions, thereby mitigating bycatch of harbour porpoises and potentially other cetacean species. As the small-scale fishery dominates in UK waters, there is an acute need for cost-effective mitigation strategies with concurrent monitoring to be implemented rapidly in order to address the problem of harbour porpoise, and more generally, cetacean bycatch.